Robot@factory lite: an educational approach for the competition with simulated and real environment - Braun, João (2020)
Teaching based on challenges and competitions is one of the most exciting and promising methods for students. In this paper, a competition of the Portuguese Robotics Open is addressed and a solution is proposed. The Robot@Factory Lite is a new challenge and accepts participants from secondary schools (Rookie) and universities. The concepts of simulation, hardware-in-the-loop and timed finite state machine are presented and validated in the real robot prototype. The aim of this paper is to disseminate the developed solution in order to attract more students to STEM educational program.